The 2008 Malaysian general elections in Sabah : Looking beyond the "peninsular factor" / Arnold Puyok - Puyok, Arnold (2008)
The 2008 Malaysian General Election saw the BN (Barisan Nasional or National Front) returned to power with less than a two-thirds majority. It has been obsei~ved that this is BN's worst electoral outing since 1969. The situation is rather different in Sabah, one of the thirteen states in Malaysia, in which BN managed to almost making a clean sweep and thus denying the opposition any chance to making inroads. Even though it was initially observed that the opposition led by PKR (Parti Keadilan Rakyat) could deny BN a major victory in Sabah, the election results indicate otherwise. At the outset, a major portion of the electorate in Sabah has renewed its support to BN, following the trend in 2004. The article argues that the tide of the "Peninsular factor" (i.e. the combined personality factor of Anwar and Mahathir and other contentious issues in the Peninsular Malaysia) give little impact on Sabah politics. It explains why the voters in Sabah give their support to BN and why they have abandoned the opposition.